A Comparative Study of Medieval Religious Spirituality: Bonaventure’s Theory of Six Stages of Spirituality and Śaṅkara’s Sixfold Practice Theory of Advaita Vedānta - Yixuan Liu (Religions, 2023)
In medieval India, the desire for “the unity of Brahman and Self” was present in the Vedānta tradition of Hinduism. Adi Śaṅkara, the master of Vedānta philosophy, proposed the six-fold sādhana: mind control, sense control, mental tranquility, endurance, potential faith, and concentration. These six-fold practices can help Vedānta followers realize unity with Brahman. In medieval Christianity, mysticism was regarded as an important path for Christians to seek a closer relationship with God. Pursuing “the unity of God and man” became the goal and direction of Christians at that time, which could be achieved through spirituality. Bonaventure, known as the Seraphic Doctor, was a representative figure of medieval Christian mysticism. He proposed six stages of spirituality: Sense, Imagination, Reason, Intelligence, Understanding, and Spark of Conscience, through which one can achieve unity with God. This article attempts to compare Bonaventure’s theory of six stages of spirituality with Śaṅkara’s idea of six-fold practice and discover the similarities and differences between Eastern and Western religious spirituality in the Middle Ages. Through this comparison, we can further explore the medieval religious believers’ desire for ultimate reality and try to find the possibility of dialogue between Christianity and Advaita Vedānta.